Climate Change Vulnerability Assessment: An Evaluation of Social Dimension - Garba, Auwal; Gana, Bukar Abba; Mohammed, Isah; Adamu, Haruna (Journal of Sustainability and Environmental Management, 2022)
Climate change vulnerability is the function of exposure, sensitivity, and adaptive capacity of its natural and socioeconomic systems. Following spatial “scale” of the assessment, administrative-territorial units were selected for this study. A field survey questionnaire was used to collect data for the study based on the sample size of 500 questionnaires that was administered to household heads in the study area. In the questionnaire, questions were designed to give respondents the opportunity to choose from several alternatives given in the instrument while descriptive statistics was for the analysis of data. Descriptive statistics analysis based on mean ranking was carried out to identify the level of peoples’ vulnerability to climate change in the study area. The exposure assessment was based on the response analysis of baseline information. The sensitivity assessment for the study was analyzed by using physiographical and socioeconomic characteristics, described by a set of specific indicators and responses of the residents. The adaptive capacity was captured by general economic and agricultural indicators, taking into consideration the major occupation the predominant lifestyle of the residents. Through a ranking approach, the relative vulnerability of each ATU was calculated by summing its sensitivity and adaptive capacity ranks; the latter were obtained as combinations of their primary indicator ranks, arranged in an increasing and decreasing order, respectively. The major climate change exposure pathway in the study area were reduction in green environment, decrease in total annual rainfall, warmer weather, early cessation of rainfall, late on-set of rainfall and shrinkage of water bodies. The major sensitivity to climate change was decrease in crop yield, whereas increase in cost of food crops, drought incidents, famine, poverty, indiscriminate falling down of trees and disaster. It was also established that the major adaptive strategies to climate change in the study area were irrigation farming, use of organic manure, planting of drought tolerant varieties and early planting.